Persepsi Pengembangan Karir Ditinjau Dari Komitmen Organisasi Pada Karyawan Kontrak - Zuraida Zuraida (Jurnal Ilmiah Psyche, 2021)
Abstract : Contract employees are employees who work at the company with a certain time limit, and can be dismissed at any time, this affects employees' perceptions of career development at the company and also affects employee commitment to the company. This study aims to examine the relationship between perceptions of career development and organizational commitment for contract employees. Perceptions of career development variables and organizational commitment were measured using a scale. The subjects of this study were 48 contract employees, with the determination of the sample based on accidental sampling. The analysis technique used in this research is quantitative analysis using Karl Pearson's product moment with SPSS version 20 for Windows. Based on the research results, it is known that the perception of career development with organizational commitment on contract employees. There is a significant positive correlation (r.0.813 with sig <0.05) between the variable perceptions of career development and organizational commitment for contract employees, namely 0.000 and the significance value is below / less than 0.05, this means that the higher (positive) the perception of career development, the higher employee commitment to the company and vice versa, the lower (negative) perceptions of employee career development, the lower employee commitment to the company. On the perception of career development has the most categories at low (negative) with a contribution of 50% and organizational commitment at most has a low category with contributions 46%. Keywords: Contract Employees, Organizational Commitment, Perceptions of Career Development. Abstrak : Karyawan kontrak merupakan karyawan yang bekerja di perusahaan dengan batasan waktu tertentu dan sewaktu-waktu dapat diberhentikan, hal ini mempengaruhi persepsi karyawan terhadap pengembangan karirnya pada perusahaan tersebut dan juga mempengaruhi komitmen karyawan pada perusahaannya. Penelitian ini bertujuan untuk menguji hubungan persepsi pengembangan karir terhadap komitmen organisasi pada karyawan kontrak. Variabel persepsi pengembangan karir dan komitmen organisasi diukur dengan menggunakan skala. Subjek penelitian ini berjumlah 48 karyawan kontrak , dengan penentuan sampel berdasarkan accidental sampling. Teknik analisis yang digunakan pada penelitian ini adalah analisis kuantitatif dengan menggunakan product moment karl pearson dengan program SPSS versi 20 for Windows. Berdasarkan hasil penelitian, diketahui bahwa persepsi pengembangan karir dengan komitmen organisasi pada karyawan kontrak, ada korelasi positif yang signifikan (r.0.813 dengan sig < 0.05) antara variabel persepsi pengembangan karir dengan komitmen organisasi pada karyawan kontrak yaitu 0.000 dan nilai signifikansinya dibawah/lebih kecil 0.05, ini berarti bahwa semakin tinggi (positif) persepsi pengembangan karir maka semakin tinggi komitmen karyawan pada perusahaannya begitu sebaliknya semakin rendah (negatif) persepsi pengembangan karir karyawan maka semakin rendah komitmen karyawan pada perusahaannya. Pada persepsi pengembangan karir memiliki kategori paling banyak pada tingkat rendah (negatif) dengan kontribusi 50% dan komitmen organisasi paling banyak memiliki kategori rendah dengan kontribusi 46%. Kata Kunci : Karyawan Kontrak, Komitmen Organisasi, Persepsi Pengembangan Karir